Ethically Aligned Mobilization of Community Effort to Reposition Shared Bikes - Liu, Zelei; Yu, Han; Wang, Leye; Hu, Liang; Yang, Qiang (Proceedings of the AAAI Conference on Artificial Intelligence, 2019)
We consider the problem of mobilizing community effort to reposition indiscriminantly parked shared bikes in urban environments through crowdsourcing. We propose an ethically aligned incentive optimization approach WSLS which maximizes the rate of success for bike repositioning while minimizing cost and prioritizing users’ wellbeing. Realistic simulations based on a dataset from Singapore demonstrate that WSLS significantly outperforms existing approaches.